AN ONTOLOGICAL PROOF OF MORAL REALISM*. Issue 1 (12th February 2014) - Huemer, Michael
Abstract The essay argues that while there is no general agreement on whether moral realism is true, there is general agreement on at least some of the moral obligations that we have if moral realism is true. Given that moral realism might be true, and given that we know some of the things we ought to do if it is true, we have a reason to do those things. Furthermore, this reason is itself an objective moral reason. Thus, if moral realism might be true, then it is true.